Double serum sampled glomerular filtration rate measurement with technetium-99m diethylenetriamine-penta acetate for evaluation of renal functions in patients with psoriasis vulgaris - Rukiye Yasak Guner; Sibel Berksoy Hayta; Melih Akyol; Zekiye Hasbek; Sedat Özçelik; Meryem Timuçin (Galenos Publishing House, 2021)
Background and Design: Psoriasis is a common chronic inflammatory skin disease believed to affect renal functions. Glomerular filtration rate (GFR) is the most important indicator used to assess renal functions. The present study aims to measure the renal function of psoriasis patients via the technetium-99m diethylenetriamine pentaacetate (Tc-99m DTPA) method and compare the values obtained with those determined through indirect measurement methods, such as the modification of diet in renal disease (MDRD) and chronic kidney disease epidemiology collaboration (CKD-EPI), considering the effects of systemic treatments and comorbidities. Materials and Methods: Eighty-seven patients diagnosed with chronic plaque-type psoriasis vulgaris were included in this study. The patients' demographic characteristics, disease duration, psoriasis area and severity index score, drugs received for psoriasis treatment, comorbidities, and drugs received for comorbidity treatment were noted. Estimated GFRs were also calculated using the MDRD and CKD-EPI formulas. Results: Tc-99m DTPA values were affected only by age. As the patient age increased, a significant decrease in GFR measured with Tc-99m DTPA (r=0.289, p<0.001) was observed. Conclusion: Psoriasis, comorbidities, and nephrotoxic drugs used for treatment did not affect renal functions. GFR measurements were affected only by age.